Role of Interventional Techniques in the Management of Cancer Pain - Sharma, Abhishek; Thakur, Niketa; Thakur, Abhishake; Bhardwaj, Neha (Asian Pacific Journal of Cancer Care, 2023)
Pain is the major cause of morbidity in cancer patients. Interventional techniques should be considered for the management of pain that is refractory to traditional analgesics or when patients are unable to tolerate opioids. Interventional techniques are intended to stop pain signals through neural pathways from the periphery to the brain. This article deals with major interventional pain management techniques such as central neuraxial block, sympathetic block, peripheral nerve block, percutaneous cordotomy, percutaneous vertebroplasty and kyphoplasty, radiofrequency ablation, and cryoablation. Besides this, the role of radiotherapy and radionuclides in cancer pain have also been discussed. Central neuraxial block can effectively reduce pain while preventing opioid toxicity. It involves a percutaneous epidural or intrathecal catheter, an external syringe pump, or a fully implanted intrathecal drug delivery system to give medication. Sympathetic blocks such as celiac plexus and superior hypogastric block have role in patients with visceral abdominal pain. Peripheral nerve blocks may be employed when the distribution of somatic pain is restricted to a single nerve or plexus. Percutaneous cordotomy could be useful for any unilateral cancer pain below C4 dermatome. Percutaneous vertebroplasty (PV) treatment is used to alleviate axial back pain due to osteoporotic wedge fracture or malignant vertebral body disease. RFA and cryoablation techniques are now widely used for back pain due to osteoporotic and malignant vertebral collapse that are resistant to conservative treatment. External beam radiotherapy and radionuclides are useful in relieving cancer pain due to bone metastasis. This article aims at summarizing the indications, mechanisms, drug agents, contraindications, and complications of interventional pain management techniques that may offer benefits to patients coping with cancer and its terrible symptoms. Even though there is some risk involved with the techniques discussed in this article, the advantages of reduced pain and enhanced quality of life usually outweigh the risk.